The selective effect of the image of a hand on visuotactile interactions as assessed by performance on the crossmodal congruency task. - Igarashi, Y; Kimura, Y; Spence, C; Ichihara, S (2008)
Seeing one's own body (either directly or indirectly) can influence visuotactile crossmodal interactions. Previously, it has been shown that even viewing a simple line drawing of a hand can also modulate such crossmodal interactions, as if viewing the picture of a hand somehow primes the representation of one's own hand. However, factors other than the sight of a symbolic picture of a hand may have modulated the crossmodal interactions reported in previous research. In the present study, we examined the crossmodal modulatory effects of viewing five different visual images (photograph of a hand, line drawing of a hand, line drawing of a car, an U-shape, and an ellipse) on tactile performance. Participants made speeded discrimination responses regarding the location of brief vibrotactile targets presented to either the tip or base of their left index finger, while trying to ignore visual distractors presented to either the left or right of central fixation. We compared the visuotactile congruency effects elicited when the five different visual images were presented superimposed over the visual distractors. Participants' tactile discrimination performance was modulated to a significantly greater extent by viewing the photograph of a hand than when viewing the outline drawing of a hand. No such crossmodal congruency effects were reported in any of the other conditions. These results therefore suggest that visuotactile interactions are specifically modulated by the image of the hand rather than just by any simple orientation cues that may be provided by the image of a hand.